Adeno‐associated virus 8‐mediated gene therapy for choroideremia: preclinical studies in in vitro and in vivo models. (May 2014) - Black, Aaron; Vasireddy, Vidyullatha; Chung, Daniel C.; Maguire, Albert M.; Gaddameedi, Rajashekhar; Tolmachova, Tania; Seabra, Miguel; Bennett, Jean
Abstract Background Choroideremia (CHM) is a slowly progressive X‐linked retinal degeneration that results in a loss of photoreceptors, retinal pigment epithelium and choroid. CHM, the gene implicated in choroideremia, encodes Rab escort protein‐1 (REP‐1), which is involved in the post‐translational activation via prenylation of Rab proteins. Methods We evaluated AAV8.CBA.hCHM, a recombinant adeno‐associated virus serotype 8 (rAAV8) vector, which targets retinal cells efficiently, for both therapeutic effect and safety in vitro and in vivo in a murine model. In vitro studies included western blot analyses and prenylation assays. In vivo studies included ophthalmoscopy, pupillometry, histology and immunofluorescence analysis. Results Infection with AAV8.CBA.hCHM induced the expression of REP‐1 protein in a dose‐responsive fashion. Transduction with AAV8.CBA.hCHM reverses the biochemical and pathogenetic defects in CHM both in vitro and in vivo and showed no safety concerns in the in vivo investigations performed in the present study. Conclusions AAV8 is a promising vector for human clinical gene therapy trials for choroideremia. Copyright © 2014 John Wiley & Sons, Ltd.